Polymerized Alizarin Red–Inorganic Hybrid Nanoarchitecture (PARIHN) as a Novel Fluorogenic Label for the Immunosorbent Assay of COVID-19 - Fatema Kaladari; Mahmoud El-Maghrabey; Naoya Kishikawa; Rania El-Shaheny; Naotaka Kuroda (Biosensors)
This study seeks to develop and implement a non-enzymatic fluorescent labeling for immunoassay and immunochromatographic assay (ICAs) targeting SARS-CoV-2, to meet the extensive interest and need for effective COVID-19 diagnosis. In this manuscript, we delineate the development, synthesis, and evaluation of a novel quinone polymer zinc hybrid nanoarchitecture, referred to as polymerized alizarin red–inorganic hybrid nanoarchitecture (PARIHN), which integrates an antibody for direct use in fluorescent immunoassays, offering enhanced sensitivity, reduced costs, and improved environmental sustainability. The designed nanoarchitecture can enhance the sensitivity of the immunoassay and enable rapid results without the complexities associated with enzymes, such as their low stability and high cost. At first, a chitosan–alizarin polymer was synthesized utilizing quinone–chitosan conjugation chemistry (QCCC). Then, the chitosan–alizarin polymer was embedded with the detection antibody using zinc ion, forming PARIHN, which was proven to be a stable label with the ability to enhance the assay stability and sensitivity of the immunoassay. PARIHN can react with phenylboronic acid (PBA) or boric acid through its alizarin content to produce fluorescence signals with an LOD of 15.9 and 2.6 pm for PBA and boric acid, respectively, which is the first use of a boric acid derivative in signal generation in the immunoassay. Furthermore, PARIHN demonstrated high practicality in detecting SARS-CoV-2 nucleoprotein in fluorescence (PBA and boric acid) systems with an LOD of 0.76 and 10.85 pm, respectively. Furthermore, owing to the high brightness of our PARIHN fluorogenic reaction, our labeling approach was extended to immunochromatographic assays for SARS-CoV-2 with high sensitivity down to 9.45 pg/mL.